Rhyncophorus palmarum L. (Linnaeus, 1758): A Morphological and Histological Study of the Female Reproductive System - Camargo Mathias, Maria Izabel [UNESP]; Sanchez, Pedro; Denardi, Sandra Eloisi [UNESP]; Caetano, Flávio Henrique [UNESP] (Wiley-Blackwell, 2011)
Rhyncophorus palmarum (Coleoptera) is a pest of great economic importance because of the damage caused in the plants of the Palmae family. This study showed that the female reproductive system of this beetle is composed of two ovaries of the telotrophic meroistic type invariably containing two ovarioles per ovary. Each ovariole is home to about 50 oocytes at different stages of maturation. The proximal region of the ovary is rather peculiar because it houses inside it a large quantity of bacilliform structures immersed in a glycolipoprotein substance, which has never before been described in the literature. The function of these structures is still unknown. However, it is suggested that they can function as a method of neutralizing the resistance of the plant because these insects are responsible for the transmission of the red ring disease to the palm plants. Microsc. Res. Tech. 74: 853-862, 2011. (C) 2010 Wiley-Liss, Inc.
Keywords: Rhyncophorus palmarum; female reproductive system; morphological; ovary